Incorporation of calcium sulfate dihydrate into hydroxyapatite microspheres to improve the release of bone morphogenetic protein-2 and accelerate bone regeneration - Baek, Jaeuk (2020)
In this study, hydroxyapatite (HA)-based microspheres with the ability to deliver bone morphogenetic protein-2 (BMP-2) were developed for accelerating bone regeneration. The incorporation of calcium sulfate dihydrate (CSD) in the HA matrix improved the rate of BMP-2 release from the microspheres. Under physiological conditions, the CSD fully degraded within 7 days and generated pore channels in the microspheres. The porosity and pore size of the HA–CSD microspheres after CSD degradation were 34.3% ± 4.2% and 11.5 ± 2.4 μm, respectively, significantly larger than those of the HA microspheres (23.9% ± 3.1% and 8.7 ± 0.9 μm, respectively). The increased porosity directly affected the rate of BMP-2 release from the microspheres. An in vitro experiment showed that both the BMP-2 release rate and the total amount of BMP-2 released increased considerably when incorporating the HA microspheres with CSD. BMP-2 was released slowly from the HA microspheres for up to 6 weeks. BMP-2 release was notably improved in the HA–CSD biphasic microspheres compared to the microspheres without CSD; the rate of release was 2.4-times faster due to the pores created by CSD dissolution after 7 days. Prior to animal testing, in vitro cell tests were performed to evaluate the biocompatibility of the HA–CSD microspheres. During CSD dissolution, biocompatible bone-like apatite precipitated on the cell surfaces, and preosteoblasts grew on the microspheres. In vivo experiments using a rabbit lateral femoral condyle defect model demonstrated that the level of bone regeneration was significantly enhanced by mineralization on the surface, generated additional pores as well as improved BMP-2 release behavior. The HA–CSD microspheres accelerated new bone growth to fill the entire defect in 6 weeks, corresponding to a 170% improvement in performance compared to the HA microspheres.